Effect of arbuscular mycorrhizal fungi on growth of avocado - da Silveira, Samar Velho; de Souza, Paulo Vítor Dutra; Koller, Otto Carlos (Pesquisa Agropecuaria Brasileira, 2002)
The objective of this work was to evaluate the influence of six arbuscular mycorrhizal fungi (AMF) (Glomus clarum, G. etunicatum, G. manihotis, Acaulospora scrobiculata, Scutellospora heterogama and Gigaspora margarita) on the vegetative growth, of grafted avocado plants (Persea sp.), in the rootstocks phase, grafted plant and after transplant to the orchard. The influence of AMF in avocado plants varyed according to the endophytic mycorrhiza species under study. The species S. heterogama, A. scrobiculata, G. etunicatum and G. clarum were more effective in root colonization, promoting better vegetative growth of plants on the rootstock phase, during the plant production period and after the transplanting to the orchard.